2021
DOI: 10.4236/abc.2021.114012
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and <i>in Vitro</i> Antibacterial Activity of 2-thiomethyl-benzimidazole Derivatives

Abstract: A series of novel substituted benzimidazole (7a -n) derivatives were synthesized and characterized by 1 H, 13 C Nuclear Magnetic Resonance (NMR) spectra and High Resolution Mass Spectrometry (HRMS). The substitution was done in position -1 and -2 by appropriate groups. These compounds are obtained by N-alkylation reaction with thiomethyl-1H-benzimidazole intermediates (5a -g). Design of intermediates (5a -g) was made by condensation reaction between 2-methylbenzimidazole thiourunium salt (3) and functionalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Because of the poor qualitative activity by the disk diffusion test of all 1 H -benzimidazole derivatives ( 1 – 3 ), none were further tested for MIC. Moreover, strain P. aeruginosa was not susceptible to a series of N-alkylated 1 H -benzimidazole ( 1a − g , 2a − g , and 3a − g ), similar to the results of Evrard et al (2021) . Compounds 1a – b , 2a – b , 2g , and 3a showed weak-to-moderate activity against Gram-negative bacteria ( E. coli ), with MIC values ranging from 64 to 1024 μg mL –1 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Because of the poor qualitative activity by the disk diffusion test of all 1 H -benzimidazole derivatives ( 1 – 3 ), none were further tested for MIC. Moreover, strain P. aeruginosa was not susceptible to a series of N-alkylated 1 H -benzimidazole ( 1a − g , 2a − g , and 3a − g ), similar to the results of Evrard et al (2021) . Compounds 1a – b , 2a – b , 2g , and 3a showed weak-to-moderate activity against Gram-negative bacteria ( E. coli ), with MIC values ranging from 64 to 1024 μg mL –1 .…”
Section: Resultssupporting
confidence: 86%
“…Moreover, strain P. aeruginosa was not susceptible to a series of N-alkylated 1 H -benzimidazole ( 1a − g , 2a − g , and 3a − g ), similar to the results of Evrard et al (2021). 50 Compounds 1a – b , 2a – b , 2g , and 3a showed weak-to-moderate activity against Gram-negative bacteria ( E. coli ), with MIC values ranging from 64 to 1024 μg mL –1 . The findings revealed that these 1-alkyl-2-(substituted phenyl) benzimidazole derivatives may be ineffective at inhibiting the growth of Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…22 and Pseudomonas aeruginosa ATCC 27853. 23 Twelve (12) N-alkyl 2-benzylthiomethyl-1H-benzimidazole derivatives were evaluated and their antibacterial profile was determined with minimal inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs). The results showed that compounds 8a, 8b, 8c, 8d, 8e, 8f, 8h, 8k, and 8l were potent against Escherichia coli and Staphylococcus aureus, with significant MICs values from 140 to 290 µg/mL.…”
Section: Biological Activities Of Benzimidazole Derivatives a Antimic...mentioning
confidence: 99%
“…Many of the prepared derivatives have efficacy comparable or superior to the standard drugs used for the same purpose. [138][139][140][141][142][143][144][145][146][147][148][149][150][151][152][153]…”
Section: Review Synopenmentioning
confidence: 99%